"We had support from our brothers": a critical race counter-narrative inquiry into second-generation Black Caribbean male youth responses to discriminatory work pathways. Issue 4 (19th May 2019) - Briggs, Anthony Q.
ABSTRACT: Drawing upon interview narratives and analysis based on Critical Race Theory, this manuscript uses a qualitative phenomenological approach to oppose one-dimensional perspectives concerning the social, educational and occupational careers of Black men who are stereotyped as lazy, criminal, dangerous and uncivil. This manuscript examines the counter-narratives of 10 second-generation Caribbean Black Male Youth (CBMY) between the ages of 18–27 currently employed in precarious positions in the City of Toronto. Drawing upon material from one-on-one interviews with the participants, this paper critically examines the lived experiences of CBMY as expressed through their own voices. While the participants offer diverse perspectives on the challenging high school-to-work transition, a common thread of resistance and brotherhood is revealed through the repeating themes of solidarity, compassion, respect, trust and mutual encouragement in the pursuit of full-time employment and a quality life.